Karakteristik Kimiawi dan Potensi Pemanfaatan Dunaliella salina dan Nannochloropsis - Radyanti Darsi; Agus Supriadi; Ade Dwi Sasanti (Jurnal FishtecH, 2012)
The objective of this research was to know the chemical characteristics and the potential utilization of D.salina and Nannochloropsis sp. The research has been conducted from December 2010 until April 2012 in Technology Of Fishery Product Laboratory, Aquaculture Laboratory, Bioprocess Laboratory University of Sriwijaya and Integrated Laboratory Bogor Agricultural University. The parameters observed were biomass dry weight, proximate (moisture content, ash content,Â  protein content, fat content, and total carbohydrate content), carotenoid, and amino acids. Proximate composition of Nannochloropsis sp. obtained in this research were 58.00% ash content, moisture content 12.39%, protein content 16.17%, fat content 0.30%, total carbohydrate content 19.08%, total carotenoids 0.27 ppm, and essential amino acids (histidine, threonine, arginine , methionine, phenylalanine, valine, isoleucine, and leucine) and non-essential amino acids (aspartic acid, glutamic acid, serine, glycine, alanine, and tyrosine). As for the sample D.salina were the ash content 58.29%, water content 15.58%, protein content 17.08%, fat content 0.003%, total carbohydrate content 15.07%, total carotenoids 0.19 ppm, and essential amino acids (histidine , threonine, arginine, methionine, phenylalanine, valine, isoleucine, leucine, and lysine) and non-essential amino acids (aspartic acid, glutamic acid, serine, glycine, alanine, and tyrosine). From the results of data analysis and chemical characteristics of dry weight D.salina and Nannochloropsis sp. obtained in this study, biomass produced this research has the chemical characteristics of lower quality than the quality requirements of microalgae as an industrial raw material of food, feed, biodiesel and bioethanol.